(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
This writing is an analysis of an epistolary poem (4.) from the collection "Heroides" by Ovid and of the tragedy "Hippolytus" by Euripides. The connection between these two poetic forms can be made on the basis of the mythological tradition regarding the content. However, what enables a deeper and broader hermeneutic analysis is the possibility to connect them in terms of their structure and intertwine them into a unique poetic form. Namely, regardless of the intentio auctoris, this female letter by Ovid has an intertextual potential to become part of Euripides’ female play in a certain form of a pre-play. Furthermore, this meta collaboration between two poetic forms from different cultural provenances has the capacity to generate intergeneric similarities and dependences enabled by the letter, as a hybrid or unifying genre.